STAGNANCY OF ARABIC LESSON CURRICULUM DEVELOPMENT IN INDONESIA: AN IDEA TO SOLVE IT - Mohammad Izdiyan Muttaqin (Pondok Pesantren Modern Islam Assalaam, 2018)
This article aims to explain a little bit about the stagnancy of the development of Arabic Lesson’s curriculum in Indonesia and to give some ideas to break that stagnancy in order to increase the productivity and boost the spirit of teachers to develop the Arabic Curriculum in Indonesia. The ideas to motivate teachers were mainly taken from the article written by James Dean Brown (Brown; 2009): “Language Curriculum Development: Mistakes Were Made, Problem Faced, and Lessons Learned”. The author also refers to some books and articles to get more informations about the Language Curriculum Development. This article ends with the conclusion that the Arabic Curriculum in Indonesia needs to be developed. And the management of schools and courses could take some actions to motivate the teachers to take a part in Arabic Curriculum Development, such as giving a special schedule for teachers to develop their curriculum, and to give teachers a forum to discuss about developing their curriculum, these steps have been implemented in some institutions, and in general, it has positive resultsArabic,